Effect of Pore-Water Salinity on the Electrical Resistivity of Partially Saturated Compacted Clay Liners - Yi Lu; Hossam Abuel-Naga; Qais Al Rashid; Md Farhad Hasan (Advances in Materials Science and Engineering)
The aim of this paper is to investigate the effect of pore-water salinity on the electrical resistivity (ER) of different compacted clay liners (CCLs) in terms of its mineralogical composition. For this purpose, an experimental programme was conducted where ERs of different kaolin-dominant CCL specimens, reconstituted using water having different concentrations of NaCl (0 M, 0.5 M, and 1.0 M), were measured. The kaolin-dominant CCL specimens tested in this study include pure kaolin, three different kaolin-bentonite mixtures, and three different kaolin-sand mixtures. The experimental results show that the ERs of CCL specimens decrease as the salt concentrations in pore water, moisture content, and dry density increase. At constant density and moisture content, the test results also indicate that increasing the sand content in kaolin-dominant CCL specimens increases its ER regardless of the water salinity level. This behaviour could be attributed to the lower surface conduction of sand compared to kaolin. However, at constant density and moisture content, increasing the bentonite content in kaolin-dominant CCL specimens decreases its ER in the distilled water environment as surface conduction of bentonite is higher compared to that of kaolin. On the contrary, in saltwater environments, ER increases as the bentonite content increases. This behaviour could be explained in terms of the expected aggregated microstructure of bentonite in the saltwater environment that could reduce the number and area of interparticle contacts, and consequently, increase the ER of CCL specimens.